2018
DOI: 10.1002/ijc.31279
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor‐infiltrating lymphocytes in nondisseminated nasopharyngeal carcinoma: A large‐scale cohort study

Abstract: The American Joint Committee on Cancer (AJCC) staging system is inadequate for an accurate prognosis in nasopharyngeal carcinoma (NPC). Thus, new biomarkers are under intense investigation. Here, we investigated whether the density of TILs could predict prognosis in NPC. First, we used 1490 cases of nasopharyngeal carcinoma samples from two independent cohorts to evaluate the density and distribution of tumor-infiltrating lymphocytes (TILs). Second, in one cohort, we assessed associations between TILs and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 29 publications
11
81
0
Order By: Relevance
“…Previous clinical studies have demonstrated that NPC is densely infiltrated by T cells [45], where the presence of more TIL, particularly CD3 + T cells, was associated with favorable outcomes [46,47]. In our model, TIL was detected in the humanized mice, and the percentage of intratumoral T cells was lower than those in circulation and spleen.…”
Section: Discussionmentioning
confidence: 57%
“…Previous clinical studies have demonstrated that NPC is densely infiltrated by T cells [45], where the presence of more TIL, particularly CD3 + T cells, was associated with favorable outcomes [46,47]. In our model, TIL was detected in the humanized mice, and the percentage of intratumoral T cells was lower than those in circulation and spleen.…”
Section: Discussionmentioning
confidence: 57%
“…Abbreviations: (+ and -) are number of positive and negative patients, *P values in bold represent significant data as calculated using χ 2 or Fisher's Exact Tests, ♣ Numbers between brackets are the percentages of patients Several studies have shown the prognostic value of TIL in various types of solid tumors [9], including Head and Neck cancers [10], and more specifically, NPC [11][12][13][14], although their studies were not devoted to LA-NPC. Wang et al [13] and Almangush et al [15] have studied total TIL in NPC using H&E stained sections and found a high correlation between total TIL and disease outcome using a large cohort (1490 patients). On the other hand, Zhu et al [14], Lu et al [11], and Ono et al [12] investigated specific TIL like CD3+ and/or CD8+ TIL on survival of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…13,[23][24][25] The 149 features included count ratio, nucleus perimeter, and Nucleus: Hematoxylin OD. About the count ratio, Ma et al 26 found that tumor-infiltrating lymphocytes (TILs) were independent prognostic indicators for disease-free survival (DFS) in NPC. Pathologists have observed that NPC tumor cells have obvious morphologic variations, with cells that are small and round, large and round, spindle-shaped, with or without vesicular nuclei, or mixed round and spindle-shaped.…”
Section: Discussionmentioning
confidence: 99%